«Euroregions»: Cooperation, cohesion and resilience - Cristina García Nicolás (Revista Galega de Economía, 2022)
The paper tackles the definition of Euro Regions in the context of cross-border cooperation that favours the three dimensions of cohesion: economic, social and territorial. With a descriptive approach, the objective of this work is to place the Euro Regions in the current climate, in which they face two important challenges: on the one hand, the need for similar levels of governance that favour decision-making on both sides of the border, and, on the other, the legal obstacles in relation to mobility and economic activity that Covid-19 restrictions have highlighted. European funds constitute an opportunity for resilience against all territories concerned, for which, even if the border is shared, brings about the difficulty of establishing a single roadmap given both geographical and socioeconomic diversity.